Human behavior, communities, organizations, and groups in the macro social environment - Kirst-Ashman, Karen Kay (Thomson/Brooks/Cole, 2008)
Includes bibliographical references (p. 387-405) and index (p. 406-414); Neal A. Newfield, Ph.D., LICSW (Giver)